Before they pass away. De verhalen achter de foto’s. Hannelore Vandenbussche. Uitgeverij Brandt, Amsterdam, 2015 - Van Damme, Patrick (Afrika Focus, 2016)
Before they pass away is ‘ [A] historic volume [that ]showcases tribal cultures around the world. With globalization, these societies are to be prized for their distinctive lifestyles, art and traditions. They live in close harmony with nature, now a rarity in our modern era. Jimmy Nelson not only presents us with stunning images of customs and artifacts, but also offers insightful portraits of people who are the guardians of a culture that they – and we – hope will be passed on to future generations in all its glory. Nelson’s large-plate eld camera captures every intricate detail and ne nuance for posterity. What’s more, this splendid pageantry is set against a vivid backdrop of some of the world’s most pristine landscapes’.